The effectiveness of orientation programme in the department of immigration Malaysia / Farhana Yaakub - Yaakub, Farhana (2009)
Due to the global world, the service sector should be more effective and competitive m fulfill the need of customers. The effective orientation programme is important in order to prepare the new employees to be ready to perform their task and responsibilities. This study consist the reviewed of the effectiveness of orientation programme in the Department of Immigration Malaysia. This study provides the information on the orientation programme that held by this department due to assist this department to improve their current orientation programme. 80 respondents (80% from the population) were involved in this study which comes form three different divisions that reached the Department of Immigration Malaysia, Kota Kinabalu Sabah. However, this study look the orientation programme as general while the orientation programme was differently created in centralized orientation programme in Academy of Immigration Malaysia (AIMM) and the initiatives orientation programme the held by the state department. Some recommendations also stated in the end of the report in assist this department to improve the programme.